A Muscle-First, Electromechanical Hybrid Gait Restoration System in People With Spinal Cord Injury - Nandor, Mark; Kobetic, Rudi; Audu, Musa; Triolo, Ron; Quinn, Roger (Frontiers in Robotics and AI, 2021)
The development of a hybrid system for people with spinal cord injuries is described. The system includes neural stimulation to activate the user’s otherwise paralyzed muscles, an exoskeleton with electromechanical actuators at the hips and knees, and a sensory and control system that integrates both components. We are using a “muscle-first” approach: The person’s muscles are the primary motivator for his/her joints and the motors provide as-needed power assistance. This design philosophy has led to the development of high efficiency, low friction joint actuators, and feed-forward, burst-torque control. Bench testing was performed to assess the performance of the actuators and it was found that hip and knee robotic actuators produce 36 Nm peak torque. The torque required to backdrive them is less than 6 Nm at all joint speeds. The system was tested with able bodied participants to verify its function and safety and then with participants with spinal cord injury (SCI). All of the able bodied users could walk at 1.2 m/s without any motor assistance, and users with SCI walked at 0.36 m/s with motor contribution. The system was found to satisfy the main design requirements as laid out at the outset.